Implementasi Peran Audit BPK terhadap Pegauditan Keuangan Daerah dalam Sistem Pengelolaan dan Pendapatan di Kabupaten Manggarai Barat Kota Labuan Bajo - Theresia Muhul; Marcelina Jemaan; Felisia Celin; Afrandi Gandur; Marianus Tito; Purnama Baso (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Regional financial management in Indonesia continues to face challenges related to transparency, accountability, and the effectiveness of internal control, despite regular external oversight carried out by the Audit Board of Indonesia (BPK). These issues are also reflected in the financial governance of Manggarai Barat Regency, an area experiencing rapid economic growth driven by the development of Labuan Bajo as a national tourism destination. This study aims to examine the role of BPK’s audit in strengthening the quality of regional financial reporting and improving revenue governance in Manggarai Barat. Using a descriptive qualitative approach and a case study design, the research analyzes audit documents, relevant regulations, and secondary literature to understand the audit process, key findings, and the extent of follow-up actions taken by the local government. The results show that the Regency has consistently received an Unqualified Opinion (WTP), indicating compliance with Government Accounting Standards. However, BPK still identified several weaknesses, particularly related to inadequate work volume, uncollected late penalties, and overpayments in certain local government units. These findings highlight that, although formal financial reporting is sound, operational practices require further improvement. BPK’s recommendations have encouraged the strengthening of internal control, better administrative discipline, and improvements in the management of regional revenue. Overall, the audit plays an essential role in guiding the local government toward more transparent, accountable, and effective financial governance.